Software Development Data Analysis and Processing under the Internet of Things Monitoring System - Junru Li; Lijuan Zhang; Xiaoqing Tang (Journal of Control Science and Engineering)
In order to solve the problem of highly extensible vibration test data acquisition and analysis, the author proposes a method for software development data analysis and processing under the Internet of Things monitoring system. The software platform is mainly designed through the design of software architecture based on multitask operation, active window design, reserved API interface and hardware universal design; it ensures the strong expansibility of the software platform, so as to realize the universality of the software platform. High-level vibration data analysis software designed based on this platform, such as modal parameter identification and dynamic load identification software, can be easily redeveloped by using the existing functions and software architecture of the platform, expand software functions, realize more complex vibration data analysis and processing, reduce repetitive labor, and speed up the software development process. The results showed that: the amplitude error is less than 4%. Conclusions. The feasibility and availability of software development data under the IoT monitoring system are verified.